Case report: Effectiveness of brexpiprazole and esketamine/ketamine combination: A novel therapeutic strategy in five cases of treatment-resistant depression - Chan, Lai Fong; Woon, Luke Sy-Cherng; Mohd Shukor, Nuur Asyikin; Eu, Choon Leng; Ismail, Nurazah; Chin, Song Jie; Nik Jaafar, Nik Ruzyanei; Baharudin, Azlin (Frontiers in Psychiatry, 2022)
A significant proportion of patients with treatment-resistant depression do not attain functional recovery despite administration of multiple steps of pharmacotherapeutic strategies. This highlights the elusiveness of meeting unmet needs in existing pharmacotherapies for treatment-resistant depression. There is accumulating evidence that antidepressant agents involving the glutamatergic system such as brexpiprazole and esketamine/ketamine have more rapid onset of action and potentially improved effectiveness as an augmentation therapy in treatment-resistant depression. This case series aimed to report five complex cases of unipolar and bipolar treatment-resistant depression where conventional treatment strategies were inadequate in managing high risk suicidal behaviour and achieving functional recovery. We discussed further the possible synergistic mechanisms of the novel combination strategy of brexpiprazole and esketamine/ketamine, clinical and patient factors that influenced treatment response, challenges with this combination strategy and implications for future practice and research.